Free Market Tuberculosis : Managing Epidemics in Post-Soviet Georgia - Koch, Erin (Book collections on Project MUSE., 2013)
The Soviet health care infrastructure and its tuberculosis-control system were anchored in biomedicine, but the dire resurgence of tuberculosis at the end of the twentieth century changed how experts in post-Soviet nations - and globally - would treat the disease. As this book demonstrates, market reforms and standardized treatment programs have both influenced and undermined the management of tuberculosis care in the now-independent country of Georgia. The alarming rate of tuberculosis infection in this nation at the crossroads of Eastern Europe and Asia cannot be disputed, and yet solutions to attacking the disease are very much debated. Here, an anthropologist explores the intersection of the nation's extensive medical history, the effects of Soviet control, and the highly standardized - yet poorly regulated - treatments promoted by the World Health Organization. Although statistics and reports tell one story - a tale of success in Georgia - the author's ethnographic approach reveals all facets of this cautionary tale of a monolithic approach to medicine. This book is the 2011 recipient of the annual Norman L. and Roselea J. Goldberg Prize for the best project in the area of medicine. -- Description provided by publisher.